Pengaruh Tingkat Pengangguran Terbuka Terhadap Tingkat Kemiskinan Di Kabupaten/Kota Kalimantan Tengah - Tarsis Ronald Parulian; Alexandra Hukom (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of the specific analysis is expected to be able to convey comprehensive knowledge of the condition of the TPT alliance and poverty in Central Kalimantan, to provide support towards expanding the benefits that contribute to reducing TPT and poverty in this region. Comprehensive quantitative methods to investigate the Central Kalimantan Open Unemployment Rate (TPT) against squalor creates a very precise and constructive approach towards gathering and reviewing instructions in an objective and measurable manner. The low educational level and restrained skills make it difficult to find a decent pulse, forcing the people of Central Kalimantan to fall into poverty. Women are more discreetly concerned with matching decent pulses and retain restricted access to the core economic power as world and capital, which can allow the more prone to slump to the depths of squalor in this region. Other social impacts of algae are reduced social capital, increased crime rates, and reduced quality of life. The economic impact can arise in part in the form of loss of economic reliability, low rewards of legion of duty participation and low economic motivation. The high number of published unemployment (TPT) in Central Kalimantan contributes to increasing poverty and the components of tutorials, skills, sexual lameness, social and economic effects are flowering. TPT embodies important components that must serve as components